The Effect of a Proposed Program Based Guided Inquiry on Algebraic Understanding Among 8th Female Graders of Different Mathematical Self-Concepts - Quttaneh, Ghdeer W.; El-Shara, Ibrahim A. (Dirasat: Educational Sciences, 2025)
Objectives: This study aimed to investigate the effect of a proposed instructional program based on guided inquiry on algebraic understanding among eighth-grade female students with different levels of mathematical self-concept. Methods: The study adopted a quasi-experimental design with two groups, experimental and control. The sample consisted of (50) students who were randomly assigned to the two groups: 26 to the experimental group and 24 to the control group. Results: The findings revealed a statistically significant difference at (α = 0.05) in algebraic understanding attributable to the teaching method, in favor of the experimental group. However, the study showed no statistically significant difference at (α = 0.05) in algebraic understanding attributable to the interaction between the teaching method and mathematical self-concept. Conclusion: It appears that the use of guided inquiry-based programs improves algebraic understanding, and that the effect of guided inquiry is independent of students’ level of mathematical self-concept. The study recommends developing training programs for mathematics teachers focused on implementing guided inquiry-based lessons and providing a supportive and safe learning environment that encourages students to inquire, experiment, and collaborate.